Composition and Thermal Structure of the Upper Troposphere and Lower Stratosphere in a Penetrating Mesoscale Convective Complex Determined by Satellite Observations and Model Simulations. (16th October 2017) - Shi, Chunhua; Cai, Wenyi; Guo, Dong
Abstract : We describe here the composition and thermal structure of the upper troposphere and lower stratosphere during a penetrating mesoscale convective complex (MCC) event that occurred in southern China on 8 June 2009. Our results are based on satellite observations and Weather Research and Forecasting model simulations. Ice-rich and ozone-poor air reached as high as 17 km. The air was −5°C colder inside the mature MCC than outside at the first cold-point tropopause near 17 km, −2°C colder inside the mature MCC than outside at the second cold-point tropopause, and 3°C warmer inside the mature MCC than outside between the two cold-point tropopauses. Corresponding to the temperature structure, there were two lower water vapor contents inside the MCC than outside near 17 km and 19 km while there was a higher water vapor content inside the MCC than outside near 18 km.